SOURCE ROCK POTENTIAL AND DEPOSITIONAL ENVIRONMENT OF OIL SHALE BASED ON PETROGRAPHY CHARACTERISTICS AND ORGANIC GEOCHEMISTRY IN KAPUR IX, WEST SUMATRA - Rahmola, Wiryadi Rizkiputra; Syafri, Ildrem; Winantris, Winantris; Suwarna, Nana (Journal of Geological Sciences and Applied Geology, 2018)
The research area were located in the Kapur IX District, Lima Puluh Kota Regency, West SumatraProvince. The research focused on Kapur IX Intramontane Sub-basin filled with oil shale. Theanalysis was carried out on shale samples of the Kapur IX Intramontane Sub-basin collected fromoutcrops to evaluate the source rock characteristics, including type of oil shale, depositionalenvironment, and dispersed organic matter. Geochemical analyses include total organic carbon(TOC) and Rock-Eval Pyrolysis, while organic petrographic analysis comprises organic materialcomposition and vitrinite reflectance. Based on the results the oil shale of the study area has lowto excellent quality and richness, type II and II kerogen content, with the maturity level of lateimmature to early mature. The dominant lamalginite maceral content in the sample tends toindicate the oil shale in the research area is a Green River type. The liptinite maceral group isdirectly proportional to the value of Potential Yield (PY) indicating that the maceral group, especiallyalginite plays a role in producing hydrocarbons in the oil shale of the study area. Based on thecomposition of maceral data, the depositional environment of oil shale of the Kapur IXIntramontane Sub-basin is interpreted to be a lacustrine environment with brackish watercondition.